Effects of different skin processing conditions of Japanese sweet potato powder (Ipomoea batatas) on physicochemical properties - Shaari, Nurfarhana; Mnemoi, Farizade; Shamsudin, Rosnah; Mohd Nor, Mohd Zuhair; Hashim, Norhashila (HH Publisher, 2021)
Sweet potato (Ipomoea batatas) is among the most popular crop around the world. Physicochemical properties are an important element in the sweet potato processing industry. However, little knowledge is known about this variety of sweet potatoes. In this study, colour, moisture, ash, protein, fat, crude fibre and carbohydrate were studied subjected to three different conditions of Japanese sweet potato; whole tuber (C1), peeled tuber (C2) and skin of tuber (C3). Colour and proximate analysis were determined using the lightness (L), red/green (a) and yellow/blue (b) system and AOAC method, respectively. The result indicated that L, a* and b* ranged from 68.0–89.2, 0.48–5.65 and 11.67–13.27, respectively. The highest values of L, a and b were observed in C1, C3 and C1, respectively. Moisture, ash, protein, fat, carbohydrate and fibre were ranged from 5.93–7.86%, 2.64–8.11%, 4.64–5.47%, 0.06–0.70%, 65.96–86.96% and 1.00–2.43%, respectively. C1 had the highest value of moisture content while C2 showed to have the highest values of protein and carbohydrate. C3 was observed to have the significantly highest (p < 0.05) content of ash, lipid and crude fibre. Overall, the differences in the physicochemical properties of three different conditions of sweet potato are significant in certain properties. C1 was suggested to be the best selection for producing better quality sweet potato products. Therefore, the result obtained from this study becomes useful for further processing of sweet potatoes.